PENGEMBANGAN KEGIATAN EKSPLORASI DENGAN MEMANFAATKAN TEKNIK QUILLING DI PAUD - Niat Jelita Gulo; Dewi Fitria; Juli Yanti Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to see the validity of Exploration Activities by Utilizing Quilling Techniques in PAUD at KB Rahva Delitua. Research and Development is a type of research and development (R&D) using phases with the ADDIE model consisting of 5 stages with stages (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. (evaluation). The focus of this research is the development of exploration activities using quilling techniques that are accompanied by guidelines as material for activities in improving fine motorics of early childhood. Instruments used to gather data are the lifts or questionnaires given to the validators, i.e. the material expert validator, and the activity expert validators. The interview instruments given to teachers before and after conducting exploration activities using quiling techniques in PAUD developed in this research. Based on the validation results of the validator, the material expert obtained an evaluation response of 13 questions received a score of 89% in the category “Very Worth”, and the evaluation result of the activity validator obtaining a evaluation answer of 15 questions obtains a rating of 86.1% in the categories “Worthful”. Based on the evaluation score criteria, it can be said that the Development of Exploration Activities Using Quiling Techniques in PAUD, is valid and very worthy to be used in the early childhood learning process